Bibliometric analysis of individualism-collectivism - Yassar, Muhammad Naufal Elian (Priviet Social Sciences Journal, 2026)
The cultural dimension of individualism-collectivism has been understood as one of the determining factors of individual psychological aspects. Research on the cultural dimensions of individualism-collectivism has been widely conducted. However, no research has been conducted on this cultural dimension using bibliometric analysis. This study employs a bibliometric research design. This study concludes that the United States (country data), The Hong Kong Polytechnic University (institution data), Gavreliuc, Alin and Vignoles, Vivian L (author data), and collectivism (keyword data) are the most influential data in the development of research on individualism-collectivism published in the Scopus database. We also found that several keywords are not connected, reflecting a research gap in the context of individualism-collectivism.